Strategic scheduling of urea foliar application and irrigation for moth bean: a path to improve Productivity, profitability and quality in Western dry region of India - Ram Lal Jat; Lalit Kumar Rolaniya; Narendra Kumar; Raja Ram Choudhary; Monika Punia; Sudheer Kumar; Arun Kumar; Rajendra Kumar Jakhar; Rajan Bhatt; Saud Alamri; Manzer H. Siddiqui (Cogent Food & Agriculture)
In the western arid regions, where monsoon seasons often include regular and extended dry spells, agricultural practices need to be tailored to these challenging conditions. This research aimed to understand the effects of foliar urea application and different irrigation scheduling on crop productivity, profitability, and quality in arid region, and was conducted over two consecutive Kharif seasons of 2020 and 2021. The use of 2% urea at flowering + pod formation stages resulted in a notable improvement in yield parameters, number, weight, and buildup of dry matter. Improvement in these parameters led to significantly higher moth bean yield, by a margin of 20 – 22% as compared to other treatments. On the basis of pooled mean of two years, foliar spray of 2% urea at flowering + pod formation stages improved the protein content by 6 to 7%, protein productivity by 27–31%, physical water productivity by ∼20% and net monetary returns by 31–34% as compared to single foliar application. Similarly, irrigation at branching + pod formation stages registered higher growth parameters, grain yield (8%), profitability (13%), nutrient uptake, and residual soil fertility in moth bean as compared to other irrigation treatments. In conclusion, it is recommended that the application of urea (2%) by foliar spray at the flowering + pod formation stages and the modification of irrigation to the branching stage + pod formation stage, from the existing recommendation (flowering + pod formation), were more profitable and productive during early, prolonged dry spells with high temperatures, which are more typical in western dry regions for moth beans. Notably, it assists in fulfilling the protein needs of the vegetarian populace of western Rajasthan, India, where moth beans play a vital role in the diet.